Updated Data on Linkage to Human Immunodeficiency Virus Care and Antiretroviral Treatment Among Men Who Have Sex With Men—20 Cities, United States - Hoots, Brooke E. (J Infect Dis, 2017)
We examined differences in prevalence of linkage to care and antiretroviral (ARV) treatment among human immunodeficiency virus (HIV)–positive men who have sex with men (MSM) between 2008 and 2014 in National HIV Behavioral Surveillance. Prevalence of linkage to care increased from 79% in 2008 to 87% in 2014 (prevalence ratio [PR], 1.05; 95% confidence interval [CI], 1.03–1.07). ARV treatment increased from 69% in 2008 to 88% in 2014 (adjusted PR, 1.15; 95% CI, 1.12–1.18). Despite these increases, a large disparity in ARV treatment between white and black MSM remains. Increased resources are needed to support immediate referrals for ARV treatment for all MSM newly diagnosed with HIV.